(untitled) (World Bulletin of Management and Law, 2023)
Modern professions offered to students place high demands on the intellectual skills of employees. Information technologies, especially multimedia, provide an opportunity to develop the intellectual skills of students. With high requirements for the intellectual development of students, they occupy one of the leading positions in the international labor market. A delay in the development of intellectual skills means a delay in life. Therefore, in the professional preparation of students for the modern digital society, it is necessary, first of all, to develop their intellectual skills and teach them how to apply them in practice